Market linkages: A Way of Sustaining the Production of Amaranth in Manjolo and Sikalenge Wards of Binga District of Matabeleland North, Zimbabwe - Pepukai Manjeru; Tendai Madanzi; Jephias Matunhu; Francis Muromo; Innocent Isaac (Science and Education Publishing (SciEP), 2023)
Through a market linkages survey of grain and vegetable amaranth farmers, input suppliers, potential market as well as agricultural extension workers, this paper investigated how grain (Amaranthus hypochondriacus L.) and vegetable amaranth (A. cruentus L.) farmers in Binga District, Matabeleland North can be linked to the market to ensure the sustainable production of grain and vegetable Amaranth in Manjolo and Sikalenge wards of Binga District. Results from the survey indicate that households have a positive perception towards production and consumption of amaranth. The potential markets that is Bulawayo, Hwange and Victoria Falls are very far and the road connectivity is very poor as indicated by the poor state of the roads Supermarkets need registered companies which is a challenge dealing with the fragmented resource poor farmers, hence there is need to arrange farmers into groups. Also formal markets normally need produce that meets certain standards hence the farmers in the two wards face the challenge in selling their produce to the formal market. The study recommends the popularisation of the vegetable by all stakeholders as well as exploration of value addition and beneficiation to tap into international markets.